Interaction of ARC and Daxx: a novel endogenous target to preserve motor function and cell loss after focal brain ischemia in mice - Donath, Stefan; An, Junfeng; Lee, Sabrina Lin Lin; Gertz, Karen; Datwyler, Anna Lena; Harms, Ulrike; Müller, Susanne; Farr, Tracy D.; Füchtemeier, Martina; Lättig-Tünnemann, Gisela; Lips, Janet; Foddis, Marco; et al. (Society for Neuroscience, 2016)
The aim of this study was to explore the signaling and neuroprotective effect of transactivator of transcription (TAT) protein transduction of the apoptosis repressor with CARD (ARC) in in vitro and in vivo models of cerebral ischemia in mice. In mice, transient focal cerebral ischemia reduced endogenousARCprotein in neurons in the ischemic striatum at early reperfusion time points, and in primary neuronal cultures, RNA interference resulted in greater neuronal susceptibility to oxygen glucose deprivation (OGD).TAT.ARC protein delivery led to a dose-dependent better survival after OGD. Infarct sizes 72 h after 60 min middle cerebral artery occlusion (MCAo) were on average 30±8% (mean±SD; p=0.005; T2-weighted MRI) smaller in TAT.ARC-treated mice (1ug intraventricularly during MCAo) compared with controls. TAT.ARC-treated mice showed better performance in the pole test compared with TAT.β-Gal-treated controls. Importantly, post-stroke treatment (3 h after MCAo) was still effective in affording reduced lesion volume by 20±7% (mean±SD; p˃0.05) and better functional outcome compared with controls. Delayed treatment in mice subjected to 30 min MCAo led to sustained neuroprotection and functional behavior benefits for at least 28 d. Functionally, TAT.ARC treatment inhibited DAXX–ASK1–JNK signaling in the ischemic brain. ARC interacts with DAXX in a CARD-dependent manner to block DAXX trafficking and ASK1–JNK activation. Our work identifies for the first time ARC–DAXX binding to block ASK1–JNK activation as an ARC-specific endogenous mechanism that interferes with neuronal cell death and ischemic brain injury. Delayed delivery of TAT.ARC may present a promising target for stroke therapy.